Evaluation of vaginal reconstruction using biological patches from different tissue sources - Zhang lin; Tian Yanpeng; Xiao Yanlai; Li Zhongkang; Liu Yibin; Zhang Mingle; Zhang Jingkun; Meng Li; Dai Jianwu; Huang Xianghua (生物医学转化)
Objective To evaluate the effectiveness of biological patches derived from different tissue sources for vaginal reconstruction. Methods Large animal models of vaginal agenesis were established using Bama miniature pigs through surgical removal of vaginal tissue. Small intestinal submucosa (SIS) and acellular bladder matrix (ABM) were used for vaginal reconstruction. Three months postoperatively, the reconstructed vaginal tissues were surgically removed and evaluated for tissue structure and function using histopathological staining and organ bath assays. Results Three months after reconstruction, both SIS and ABM achieved anatomical reconstruction of the vagina. Histological and functional analyses revealed that the tissue structures of SIS-and ABM-reconstructed vaginas resembled normal vaginal tissue and expressed vaginal-specific molecular markers, including CK14, α-actin, HSP47, ER, and CD31. However, the SIS-reconstructed group exhibited a thinner vaginal epithelial layer compared to the ABM-reconstructed group, indicating that ABM may provide better reconstruction outcomes. Additionally, PAS staining and organ bath assays confirmed that the reconstructed vaginal epithelial cells were capable of synthesizing glycogen and exhibited contractile and relaxant responses to corresponding drugs. These results indicated that both SIS and ABM could achieve vaginal reconstruction in terms of gross anatomy, tissue structure, and function. Conclusion Bama miniature pigs can serve as suitable large animal models for vaginal tissue regeneration and reconstruction. Both SIS and ABM can achieve anatomical, histological, and functional vaginal reconstruction, with ABM potentially offering better outcomes than SIS.